Pengaruh Penambahan Doping Vanadium terhadap Nanopartikel SnO₂ Menggunakan Metode Sol-Gel - Amsyar, Nadhilah; Sanjaya, Hary; Patriela, Miftah (Lembaga Yasin AlSys, 2025)
Semiconductors are materials used to conduct electricity for a certain period of time. SnO2 is an n-type semiconductor that has a wide band gap and is most widely used in technology such as solar cells, batteries, and catalysts. This study aims to analyze the effect of vanadium doping on the properties of SnO2 nanoparticles using the sol-gel method. The sol-gel method can produce a stable vanadium-doped SnO2 surface and has a high surface area. Determination of the band gap energy value in SnO2 was carried out by characterization using UV-DRS. The results of SnO2 doped with vanadium obtained the optimum bandgap value at the addition of vanadium with a concentration of 0.25 mmol, which is 2.25 eV and SnO2 without the addition of vanadium doping has a bandgap value of 3.41 eV. This shows that the addition of vanadium doping can affect the bandgap value of SnO2 nanoparticles. This decrease in the bandgap value is caused by the interaction between the electron band and the delocalization of electrons in the transition ions causing metal ion substitution, which results in a decrease in the bandgap value.